Brand loyalty for mobile devices from the perspective of Vietnamese culture: antecedents and moderating effects of age - Phan, Manh Dinh; Le, Tran Huynh Thi (Journal of International Economics and Management, 2024)
This study examines the correlations between brand personality, identity, perceived quality, and loyalty, as well as the moderating effect of age. The paper uses structural equation modeling and survey methodologies to present the findings. The data were collected from 228 Vietnamese respondents for the primary analysis. The research results show that brand personality, identification, and perceived quality positively affect brand loyalty. Age also negatively moderates the relationship between brand personality and brand loyalty, and positively moderates the relationship between perceived quality and brand loyalty; however, it does not moderate brand identification-loyalty connections. Additionally, brand loyalty is influenced by brand personality, identification, and perceived quality. Age moderates these relationships. The findings on the moderating effects of age are pioneering academically, especially in Vietnam. This study offers practical recommendations to address branding and marketing issues in business management. Based on moderating effects, managers and businesspeople can create marketing and branding campaigns that target the right age groups for each antecedent.